2016
DOI: 10.1016/j.expthermflusci.2015.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and utilization of catalytically cracked cashew nut shell liquid in a diesel engine

Abstract: In this study, CNSL (Cashew nut shell liquid), an economically viable feedstock among the other contemporary resources, has been considered as an appropriate source of alternate fuel.Herein, CNSL was extracted from cashew nut outer shell, a waste product, through a unique approach of steam treatment process followed by mechanical crushing technique. In contrast to the past studies that have attempted to use unprocessed CNSL directly as substitute for diesel, this study has resorted to use processed CNSL by cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Higher pressures and temperatures resulted in higher hydrogenation and deoxygenation, while at lower conditions, a high degree of cracking was reported [14]. Vedharaj et al, (2016) reported a unique method of oil extraction from cashew nutshell (CNSL) using a steam treatment assisted by a crushing technique and followed by cracking using a catalyst of zeolite. The physicochemical properties of biodiesel and their blends were determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher pressures and temperatures resulted in higher hydrogenation and deoxygenation, while at lower conditions, a high degree of cracking was reported [14]. Vedharaj et al, (2016) reported a unique method of oil extraction from cashew nutshell (CNSL) using a steam treatment assisted by a crushing technique and followed by cracking using a catalyst of zeolite. The physicochemical properties of biodiesel and their blends were determined.…”
Section: Introductionmentioning
confidence: 99%
“…The physicochemical properties of biodiesel and their blends were determined. The performance of a CI engine powered by CNSLB20 was evaluated with various injection pressures, and the results were compared with conventional fuel [15]. Velmurugan et al (2014) studied engine performance powered by thermally cracked CNSL and their blends.…”
Section: Introductionmentioning
confidence: 99%
“…CNSL is the agro waste from cashew processing industry, which is cheaper than the existing alternate fuel (that is, waste vegetable and frying oil, animal fat, plastic oil, engine lubricating oil, kapok oil in diesel engines). 1 CNSL has two different types: 1. technical CNSL and 2. natural CNSL. Technical CNSL consists of 62.86% cardanol, 11.25% cardol, 2.04% 2-methyl cardol, and 2.04% polymer, whereas 1.2% cardanol, 11.31% cardol, 2.08% 2-methyl cardol, 20.3% polymer, and 64.93% anacardic acid are present in natural CNSL.…”
Section: Introductionmentioning
confidence: 99%
“…Cardanol in cashew nut shell liquid (CNSL) is one of the potential substitutes for diesel in diesel engines. CNSL is the agro waste from cashew processing industry, which is cheaper than the existing alternate fuel (that is, waste vegetable and frying oil, animal fat, plastic oil, engine lubricating oil, kapok oil in diesel engines) …”
Section: Introductionmentioning
confidence: 99%
“…31 Promising work has been reported using many vegetable oils such as jatropha oil, jojoba oil, mahua oil, rapeseed oil etc., which have shown reasonable results as compared to commercially available mineral oils. 12,[32][33][34][35][36][37][38][39] Cashew nuts are grown in surplus in India, and thus a vegetable oil can be easily obtained 40 from cashew nuts. Cashew nut shell liquid (CNSL) is produced while processing of cashews which is produced before cardanol and thus can be considered as one of the natural substitutes to the mineral oils used in industry.…”
Section: Introductionmentioning
confidence: 99%